Peran Organisasi Moneter Internasional Dalam Pemulihan Ekonomi Sri Lanka Perspektif Hukum Ekonomi Internasional - ayu perdija ginting; Evi Deliana Hz; Ledy Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
Economic crisis of Sri Lanka is the lowest point in the history of this country, therefore chaos cannot be avoided. It makes Sri Lanka have to ask for help from The IMF, to provide financial assistance in overcoming the crisis. In accordance with the provisions of the IMF formation charter, the granting of assistance funds to member countries is one of the tasks of the IMF. However, the assistance must be accompanied by the terms and conditions that Sri Lanka must follow before finally receiving the assistance. The goal of this study is to identify the role of the IMF as an international organization that helps the Sri Lanka economy. This type of research is normative legal research, namely legal research carried out through examining library materials in the form of binding legal rules and secondary data such as other literature related to this research. As a result, according to the charter for the establishment of the IMF, the role of the IMF in providing financial assistance is in accordance with the duties of the organization and is a right for member countries. In the end the IMF did provide aid funds but the provision of these funds in reality seemed to hang Sri Lanka for about a year even though the country was in a state on the verge of collapse. The provision of assistance is also accompanied by various conditions on the grounds that the borrowing country must be able to ensure that they can return the funds according to the agreement, considering that these funds are the result of the quota of each member country. Sri Lanka as a borrowing country must follow the standards set by the IMF regarding the conditions of countries entitled to receive loans by implementing policies.